Local Government Unit’s Support to Educational Programs as Viewed by the Citizens: The Case of Lezo, Aklan - Cecilia T Reyes; Cecile O. Legaspi; Clyde G. Abayon; Tomas O. Ortega; Anna Mae. C. Relingo; Mary Eden M. Teruel; Jyanee Loi D. Yecla (International Journal of Emerging Issues in Early Childhood Education, 2021)
A study was conducted to evaluate the performance in the delivery of support to education programs of the Local Government Unit (LGU) of Lezo, Aklan. The samples were determined adopting the Multi-Stage Random Probability Sampling technique. The targeted 150 respondents were proportionately allocated in each barangay based on the 2015 Census Population and Housing Data from the Philippine Statistical Authority. The qualified sample respondents were selected using the Kish Grid. Female respondents were targeted for even numbered questionnaires while male respondents were targeted for odd numbers. The four major core concepts namely awareness, availment, satisfaction and need for action were used in measuring the rating of the respondents and presented in frequency and percentage distributions. The reasons for their response were likewise gathered. The study concluded that most of the respondents were not aware of scholarships and other assistance programs for students and alternative learning system and other special education programs. Low adjectival rating of citizens availment on educational programs was noted from the survey. This implies that there is a need for considerable improvement and significant interventions for the citizens to be knowledgeable and be able to avail those educational services offered in the Municipality of Lezo. In general, respondents were satisfied on educational programs. In spite of this positive feedback, additional efforts toward improvement are still essential. It is recommended that the LGU must provide budget for the construction of school buildings, libraries, and other facilities and acquisition of needed reference materials in order to provide its citizens with conducive environment for learning.